2004
DOI: 10.1177/147323000403200502
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-erbB-2 and p53 in Breast Carcinoma Patients: Comparison with Traditional Prognostic Factors and Survival

Abstract: We aimed to determine the correlations between standard clinicopathological factors and expression of c-erbB-2 and p53 proteins, and to investigate the significance of these variables in relapse and disease-free survival (DFS) in breast carcinoma patients. Data from 200 patients who had undergone mastectomy for breast carcinoma were evaluated. Significant correlations were found between c-erbB-2 positivity and high histological grade (grade 3) tumour, p53 positivity and high grade tumour, and age < 60 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the current study p53 immunostaining was positive in 38.3%. However others reported different results (7,8,9). Our study showed a significant inverse correlation with increasing age (p=0.001), with higher expression being found in younger patients and lower expression in older age group.…”
Section: Discussionsupporting
confidence: 47%
“…In the current study p53 immunostaining was positive in 38.3%. However others reported different results (7,8,9). Our study showed a significant inverse correlation with increasing age (p=0.001), with higher expression being found in younger patients and lower expression in older age group.…”
Section: Discussionsupporting
confidence: 47%
“…The co-expression of TP53 protein and ERBB2 has been extensively studied as prognostic indicator for breast cancer mainly using IHC based methods [8][9][10][11][12][13][14][15][16][17]. However, discrepancies among the study results exist, probably due to the qualitative and quantitative differences in the interpretation of IHC results.…”
Section: Survival Comparisons By Tp53 Mutation Type and Erbb2 Amplifimentioning
confidence: 99%
“…Genetic alterations of TP53 and ERBB2 are among the most common abnormalities in breast tumors, and they have been extensively studied as prognostic indicators for breast cancer. Over-expression of ERBB2 and expression of mutant TP53 proteins (mutations in TP53) have been shown to have prognostic value individually; however the prognostic significance of their co-existence in the same tumor is still controversial [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The p53 protein plays a pivotal role in the cellular response to DNA-damaging events. P53 overexpression has been correlated with higher histological breast tumour grade and lower overall and disease-free survival in breast cancer patients (Gurkan et al 2004). Bcl-2 positivity in breast tumours entails a more favourable clinical course with lower frequency of lymph node metastasis and longer survival, whereas this suggestion may not apply to the pleomorphic lobular carcinoma subtype which is a variant of ILC characterized by poor prognosis (Frolik et al 2001).…”
Section: Biological and Clinical Features Of Invasive Lobular Cancermentioning
confidence: 98%